Fjallgerður - María Arnardóttir 1989- (2019)
Fjallgerður is María Arnardóttir's graduation work from the Department of Performing Arts at Iceland University of the Arts. Fjallgerður is a monument to Hallgerður langbrók, a monument to Laugarnes, an amplification of that which has been forgotten and long since neglected and ignored. Fjallgerður is an invitation to women, an invitation to everyone; to find voice and take space. When María was a child, she used to think the most important thing in the world was to be good. As she grew up, that belief somehow stuck with her. She focused on being to others what she didn’t think she could be for herself. Hallgerður was different. As she grew up, she determinedly took the space she needed. However, her subversive behavior had repercussions. Every space she took came with consequences of her community labeling her as stubborn, wayward and disobedient. But despite her harsh labels and bad reputation she stood tall against social norms. Hallgerður stood up for herself.